PERSEPSI SISWA SMAN 1 PAYUNG TEHADAP KENAKALAN REMAJA - Sandira, Sandira (STUDIA: JURNAL HASIL PENELITIAN MAHASISWA, 2016)
The development of juvenile deliquency in Indonesia is so bad. It happened in SMAN 1 Payung. but in this two years, level of deliquency conducted by students was decrease. It caused by self-awareness of students and programs conducted by the school and teacher of guidance counseling to solve deliquency in the school environment. Through the program, it can solve and prevent the students doing deliquency. It supported by environment factor of quite school and far from noisiness, and the students are not easy affected by outside of school environment. This study aims to determine students’ perceptions about juvenile delinquency and add their insights and how students/prevent them from delinquency so they do not fall into the wrong way. This research is a research survey describes about students’ perceptions of SMAN 1 Payung on juvenile delinquency obtained by questionnaires as data collection and documentation, such as behavior in the field. Then, the data were analyzed by using analysis descriptive, namely compile the data obtained systematically categorize data related to the research and data have been collected through questionnaires were analyzed descriptively, so getting an overview of students’ perceptions of juvenile delinquency. The results of this research showed that students’ perception of juvenile delinquency assesses more negative than positive, about 80%: 20%. While the efforts made in addressing acts of delinquency students are doing positive activities, choose the correct environment, not to consume drug and avoid negative actions. Some advantages are the students can be avoided from deliquency.